2016
DOI: 10.2514/1.b35683
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Facility Effects on Hall Thruster Cathode Coupling: Performance and Plume Properties

Abstract: The impact of facility conductivity on Hall effect thruster cathode coupling is experimentally investigated. The 3.4 kW Aerojet Rocketdyne T-140 Hall effect thruster operating at a discharge voltage of 300 V, a discharge current of 10.3 A, and an anode flow rate of 11.6 mg∕s serves as a representative Hall effect thruster test bed. The nominal facility operating pressure during thruster operation is 7.3 × 10 −6 Torr corrected for xenon. Two 0.91 × 0.91 m square aluminum plates are placed adjacent to, but elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Although the current collection by the facility walls is controlled by the wall sheath and does not impact quasi-neutrality in the plume, this alternate electron recombination pathway is an artificial effect introduced by the presence of the vacuum facility that is expected to be absent on orbit. Furthermore, previous work has confirmed that the presence of this alternate pathway can alter processes dependent on the electron path through the plasma, such as cathode coupling and plasma reactance, [26][27][28][29].…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Although the current collection by the facility walls is controlled by the wall sheath and does not impact quasi-neutrality in the plume, this alternate electron recombination pathway is an artificial effect introduced by the presence of the vacuum facility that is expected to be absent on orbit. Furthermore, previous work has confirmed that the presence of this alternate pathway can alter processes dependent on the electron path through the plasma, such as cathode coupling and plasma reactance, [26][27][28][29].…”
mentioning
confidence: 83%
“…Figure 1 shows the physical location of the plates with respect to the T-40 HET. Identical plates have been used in previous studies of electrical facility effects [26][27][28][29]. The surface area of the plates represents approximately 2% of the total facility wall area.…”
Section: Configuration Of Platesmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, multiple theories behind the ground facility-thruster interactions have emerged. Frieman et al 15,16 have looked at the role of the conducting wall in facility effects and Crofton suggested that the increase in thrust could be due to charge exchange. 17 However, the fundamental manifestation of these effects still remains unidentified.…”
Section: Introductionmentioning
confidence: 99%